Effect of a water-maze procedure on the redox mechanisms in brain parts of aged rats - Krivova, Natalia A.; Zaeva, Olga B.; Grigorieva, Valery A. (Frontiers in Aging Neuroscience, 2015)
The Morris water maze (MWM) is a tool for assessment of age-related cognitive deficits. In our work, MWM was used for appraisal of cognitive deficits in 11-month-old rats and investigation of the effect exerted by training in the Morris water maze on the redox mechanisms in rat brain parts. Young adult (3-month-old) and aged (11-month-old) male rats were trained in the water maze. Intact animals of the corresponding age were used as the reference groups. The level of pro- and antioxidant capacity in brain tissue homogenates was assessed using the chemiluminescence method. Cognitive deficits were found in 11-month-old rats: at the first day of training they showed only 30% of successful MWM trials. However, at the last training day the percentage of successful trials was equal for young adult and aged animals. This indicates that cognitive deficits in aged rats can be reversed by MWM training. Therewith, the MWM spatial learning procedure itself produces changes in different processes of redox homeostasis in 11-month-old and 3-month-old rats as compared to intact animals. Young adult rats showed a decrease in prooxidant capacity in all brain parts, while 11-month-old rats demonstrated an increase in antioxidant capacity in the olfactory bulb, pons + medulla oblongata and frontal lobe cortex. Hence, the MWM procedure activates the mechanisms that restrict the oxidative stress in brain parts. The obtained results may be an argument for further development of the animal training procedures aimed to activate the mechanisms responsible for age-related cognitive deficits. This may be useful not only for the development of training procedures applicable to human patients with age-related cognitive impairments, but also for their rehabilitation.